Sleep characteristics in obesity - O. V. Lubshina; A. L. Vertkin; Ya. I. Levin (Кардиоваскулярная терапия и профилактика, 2007)
Aim. To study sleep disturbance role in obesity pathogenesis among co-morbidity-free patients. Material and methods. The study included 66 co-morbidity-free obese patients and 24 healthy volunteers. All participants underwent detailed clinical examination. Psychometrical scales for subjective self-assessment were used: subjective sleep disturbance assessment scale, hospital anxiety and depression scale; vegetative disturbance scale. Somnological function was assessed by polysomnography method. Results. Sleep pathology in obesity was registered in 86% of the patients, including 59% with sleep respiratory disturbances (RD) and typical complaints: poor quality of morning wake-up, morning headache, daytime somnolence. Falling asleep process, sleep continuity, and total sleep length were unchanged, but deep stages of slow-wave sleep (stages 3 and 4) and fast sleep phase (FSP) were deficient. In 27% of the patients, sleep RD were absent, with premature wake-ups as a typical complaint. Objectively, total sleep time reduction, falling asleep and intra-sleep vigilance time increase, sleep structure disturbance, mostly due to frequent wake-ups, decrease of deep stage slow-wave sleep and FSP were observed. No subjective or objective sleep quality disturbances were registered in 14% of the patients. Conclusion. In complex obesity treatment, differential sleep pathology correction is important, including RD management and adequate psycho-pathology therapy.